The Influence of Job Satisfaction, Organizational Commitment and Transformational Leadership on Job Performances: A Study in Higher Learning Institutions - Izah, Mohd Tahir; Muzalifah, Monil (2014)
Employees job performance including those working in higher learning institutions are becoming more important as they provide a benchmark for the institutions to excel in terms of the quality of services provided. This paper aims to examine the influence of job satisfaction, organizational commitment and transformational leadership on job performance. A structured questionnaires consisting of job performance (5 items), job satisfaction (6 items), organizational commitment (6 items) and transformational leadership (6 items) were adapted from previous research. 90 respondents from the administrative staff were chosen from selected public higher learning institutions in Malaysia. The results indicate that job satisfaction, organizational commitment and transformational leadership are significant and positively correlated with job performance. These results could be used by the relevant authorities to provide good service quality in the administration category.